Molecular interactions in solutions of poly vinyl alcohol : an ultrasonic study - Vigneswari, M; Saravanakumar, S. S; Suresh, V. N; Sankarrajan, S (International Journal of Advanced Chemistry, 2016)
Ultrasonic velocity, density, viscosity have been measured experimentally in the binary and ternary mixtures of Poly Vinyl Alcohol (PVA), water and borax with various concentration at 301.32 K. As the acoustical parameters like adiabatic compressibility, intermolecular free length, relaxation time, acoustic impedance, surface tension, Rao’s and Wada’s constant, ultrasonic attenuation and free volume would be more useful to predict and confirm the molecular interaction, these have been determined by using ultrasonic velocity, density and viscosity of the prepared solution. It has been identified that the molecular interactions in binary mixture were stronger than that of in ternary mixtures. And also there is a strong solute – solvent interaction occurring in both binary and ternary solutions. This may be due to the greater possibility of hydrogen bonding between PVA and Water molecules. When the borax is added, the molecular interaction is getting weaker due to greater affinity of borate ion towards the hydrogen in hydroxyl group of PVA.